Job Satisfaction of Supplier Company Employees: Organizational Commitment and Work Discipline - Mochamad Mochklas; Didin Fatihudin; Avif Takhul Huda (Budapest International Research and Critics University, 2021)
Supplier companies have dynamic and complex processes that require qualified human resources. Job satisfaction is important for individuals and companies, because job satisfaction is not only related to work pleasure, this study aims to determine and analyze the effect of organizational commitment and work discipline on job satisfaction of employees who work at supplier companies. This research was conducted at a hotel supply company, namely PT. Exagon. The research approach with quantitative data is processed and analyzed using the SPSS 20 program, data analysis includes validation, reliability and multiple regression analysis, t test, F test and the coefficient of determination. From the results of the analysis and discussion of this study, it can be concluded that organizational commitment has a positive and insignificant effect on employee job satisfaction, work discipline has a positive and significant effect on employee job satisfaction, and organizational commitment and work discipline have a positive and significant effect on employee job satisfaction. Positive and significant effect on job satisfaction. The results of this study are expected to increase the productivity and performance of employees who work in supplier companies and the results of this study are expected to be a reference in human resource management studies.